Near-infrared uncaging or photosensitizing dictated by oxygen tension - Erin D. Anderson (Nature Portfolio, 2016)
The generation of reactive oxygen species (ROS) in photodynamic cancer treatments is limited by low intraturmoural oxygen availability. Here the authors show that irradiation of a silicon phthalocyanine leads to uncaging of a biologically active molecule or to ROS formation in an oxygen-dependent manner.